Territory size, population density, and natural history of Cabanis’s Ground Sparrow, an endemic species found in urban areas - Juárez Jovel, Roselvy (2021)
Worldwide urban expansion threatens biodiversity inhabiting the original natural environments now being transformed, especially range-restricted species. Here, we provide estimates of population density, population size, and territory size of Cabanis’s Ground Sparrow Melozone cabanisi, a Costa Rican endemic. Additionally, we provide information about its life history. We measured abundance and estimated density using the King model. We estimated population size using density data and available habitat. We estimated territory size by following 21 pairs during the breeding season. We followed every individual for 1–3 days, for at least 1 h per day, and geo-referenced their locations. We then estimated territory size using the minimum convex polygon method. Counts and territory size observations were carried out between 06:00 and 09:00 h, when this species is most active. We summarized natural history from opportunistic observations collected during 20 years in the field as well as data from museum specimens. Bird densities range from 0.06 to 0.24 mature individuals per hectare. We estimated that the global population of Cabanis’s Ground Sparrow is between 2958 and 11,832 mature individuals. Territory size was larger at the suburban and urban sites than at the rural sites. The breeding season for this species spans 10 months with a peak in June–July. Nest architecture is less variable than that reported for other congeners. Both parents feed and defend their nestlings and provide nest sanitation. Since we found lower bird density and larger territory size at the suburban and urban sites, we propose that these represent lower-quality habitats for Cabanis’s Ground Sparrows. Given its small population size, the reduction and fragmentation of its habitats due to urbanization, and its high conservation priority assigned by the Costa Rican government, we urgently recommend a careful re-evaluation of the species’ IUCN status.